Dataset_Social_media_Smartphone_Psychological_adjustment. - Arrivillaga, Christiane; Griffiths, Mark D.; Rey-Peña, Lourdes; Extremera-Pacheco, Natalio (Universidad de Málaga, 2024)
Problematic social media use (PSMU) has become an increasingly researched area in the general population, specifically among adolescents. Due to its association with poor well-being and negative consequences, it is important to have assessment instruments that are valid and reliable in evaluating PSMU. The Bergen Social Media Addiction Scale (BSMAS) is the most widely used scale to assess PSMU. The present study analyzed the psychometric properties of a Spanish version of the BSMAS among Spanish adolescents. The sample comprised 688 adolescents from Spain (54% girls), aged 12 to 18 years (M = 14.23 years) who completed a number of self-report questions and psychometric scales. The reliability, construct validity, concurrent validity, and criterion validity of the BSMAS were evaluated. Additionally, the measurement invariance by gender and age group was also calculated. The results indicated good reliability indices (coefficients’ range = 0.75–0.83). Moreover, PSMU was positively associated with problematic smartphone use, frequency of social networking site use, depression, anxiety, and loneliness and negatively associated with self-esteem and flourishing (r range = -0.16–0.65). Furthermore, configural, metric, and scalar invariance was established among boys and girls, and younger and older adolescents. The study provides preliminary evidence indicating that the Spanish BSMAS is a reliable and valid instrument to assess PSMU among Spanish-speaking adolescents.
Keywords: Internet y jóvenes; Redes sociales en internet; Uso problemático redes sociales; Bergen social media addiction scale; Validación; España